Shigella flexneri isolation from the blood of a child with severe bacillary dysentery - Bilginturan, Nihat; Aksoycan, Namık; Akman, Muvaffak (The Turkish Journal of Pediatrics, 1961)
Sh. flexneri type 2b was isolated from the stool and from the blood culture of a seven month old girl who died of shigellosis.Since Turkish medical literature has no report of such an isolation and elsewhere it is rare, we are reporting our microbiologic findings and other indications of bacteremia as found in this case